Trans-catheter mitral valve repair in the elderly and very elderly patients with focus on postprocedural safety and 1-year effectiveness. (3rd October 2022) - Mahnkopf, C; Schnupp, S; Amami, M; Mady, H; Salloum, B; Ajmi, I
Abstract: Background and objectives: Symptomatic mitral regurgitation (MR) is associated with a high mortality rate and high heart failure-related hospitalization. Symptomatic therapy in the elderly and very elderly patients remains weak in controlling severe MR with an elevated morbidity and mortality rate. Patients with an increased risk of surgical repair of the MR seemed to benefit from MitraClip procedures. Therefore, we thought to analyze the postprocedural safety and success of the MitraClip in octogenarians and older patients. Methods: Elderly and very elderly patients with severe and symptomatic MR were presented and evaluated in the heart team. Patients with high surgical risks underwent MitraClip (Abbot, USA) procedure in our center. Post-procedural transthoracic echocardiography (TTE) procedure was performed to determine the MR grade and exclude procedure-related complications. Results: Two hundred eleven consecutive patients, older than 80 years (83.75±2.95, 106 Men (83.5±3.06) and 105 Women (84.01±2.83)), who received MitraClip between May 2015 and May 2020 were enrolled. The baseline characteristics are presented in table 1. Procedural success, defined as reducing the MR to grad I-II, was achieved in 93% of the patients (3.11±0.34 vs. 1.25±0.46, P=0.002). All patients improved in the New York Heart Association functional class (3.04±0.40 vs. 1.92±0.76) one year after the intervention. No procedure-related death was registered. 81% (n=168) survival rate was achieved one year after the intervention. No clip embolization was detected in 3 months echocardiography control, Table 2. Conclusions: Our preliminary results indicate that MitraClip is a safe and effective therapeutic option in elderly and very elderly patients with severe MR and high surgical risks. Therefore, this therapy should be considered despite age and comorbidities for effective symptomatic treatment in this particular cohort. Funding Acknowledgement: Type of funding sources: None.